2000
DOI: 10.1007/s005950050027
|View full text |Cite
|
Sign up to set email alerts
|

Altered Plasma Antigen Levels of Tissue Factor Pathway Inhibitor During Open-Heart Surgery

Abstract: Tissue factor pathway inhibitor (TFPI) is a potent inhibitor of the extrinsic pathway of the coagulation cascade that is activated by cardiopulmonary bypass (CPB) during open-heart surgery. In the present study, we investigated whether the plasma TFPI antigen increases during CPB in 12 patients who underwent bypass procedures. The plasma levels of free and total TFPI antigens were measured using an enzyme-linked immunosorbent assay, and heparin concentrations were measured using a chromogenic substrate assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…The original knowledge that the released TFPI is not associated with lipoproteins was obtained by experiments with UFH. 5,13,25,26 As recently reported by Sun et al, 27 the changes in the total plasma TFPI antigen level depended significantly on the level of free TFPI antigen after administration of UFH (r = 0.96, P <0.0001). In contrast to this, in a comparison of the release of total and free TFPI by the LMWH bemiparin, 28 the %-free TFPI ranged between 43.1 and 70.3% in dependence on the applied bemiparin dose.…”
Section: Figuresupporting
confidence: 59%
“…The original knowledge that the released TFPI is not associated with lipoproteins was obtained by experiments with UFH. 5,13,25,26 As recently reported by Sun et al, 27 the changes in the total plasma TFPI antigen level depended significantly on the level of free TFPI antigen after administration of UFH (r = 0.96, P <0.0001). In contrast to this, in a comparison of the release of total and free TFPI by the LMWH bemiparin, 28 the %-free TFPI ranged between 43.1 and 70.3% in dependence on the applied bemiparin dose.…”
Section: Figuresupporting
confidence: 59%
“…The presence of the 38 kDa fragment is probably not a result of heparin and protamine alone, as previous authors have observed that protamine rapidly and completely reverses the effect of unfractionated heparin on plasma TFPI activity [13]. Our findings are consistent with the findings of Sun et al [30], who demonstrated a persistent elevation of free TFPI following CPB, and suggest that TFPI undergoes proteolytic degradation during CPB. Plasma TFPI may play an important role in heparinmediated suppression of coagulation activity during CPB.…”
Section: Discussionsupporting
confidence: 92%
“…Preheparinization of the donor efficaciously increased total plasma TFPI levels by a factor of 8.0 when compared to the nonheparinized blood. It has been documented that total plasma TFPI levels strongly correlate with the levels of free plasma TFPI during CPB . This heparin‐induced TFPI elevation completely counterbalanced the production of both TAT and F 1+2 boosted by rTF.…”
Section: Discussionmentioning
confidence: 92%
“…TFPI directly inhibits TF/VIIa complex and activated factor X (Xa). Previous studies have demonstrated that heparin administration causes endothelial release of TFPI, which increases serum concentrations by twofold to tenfold within minutes . It has been postulated that heparin suppresses the TF‐dependent coagulation pathway during CPB by releasing TFPI.…”
mentioning
confidence: 99%